Apples to apples: Comparing BRT and light rail while avoiding the "BRT-Lite" trap. (October 2018) - Levine, Jonathan; Singer, Matan; Merlin, Louis; Grengs, Joe
Highlights: On a per-exclusive-guideway-km basis, LRT capital costs are about double those of BRT. As BRT guideways become more complex, their guideway costs tend to converge with those of LRT. The main difference in capital costs between BRT and LRT is in Professional Services. BRT running on exclusive ROW provides service competitive with that of the automobile and LRT. LRT support is partly shaped by a common alternative: BRT-lite with little dedicated right of way.